(untitled) (JED (Jurnal Etika Demokrasi), 2021)
Abstract. The substance problem in this study is the demoralization of the religious character of students, so it requires a more comprehensive model of strengthening character education. The research objective is to produce an integrated model for the development of moral integrative-based religious character education. The research used a mix-method, namely a combination of qualitative methods and quantitative methods. The qualitative research instrument uses the researcher himself as the main instrument while the quantitative instrument uses a validated questionnaire. Research informants, qualitative research using purposive sampling and random sampling techniques for quantitative research. Data collection techniques using interview techniques, observation techniques, questionnaire techniques and documentation techniques. The stages of qualitative data analysis were carried out by starting to reduce data, display data, and verify data. The results of the research on the integration model of the development of religious character education that has been developed at the University of Muhammadiyah Makassar are integrated with the moral integrative, namely knowing, feeling, sinverbal, action, habitus and culture to instill religious character in students in six moral levels starting from moral knowing, moral feeling, moral. sinverbal, moral action, moral habitus and moral culture at the student and academic community level at the University of Muhammadiyah Makassar. Keywords: Character Education, Moral sinverbal, Moral habitus, Moral culture, Students Abstrak. Masalah substansi pada penelitian ini adalah demoralisasi karakter religius mahasiswa, sehingga membutuhkan suatu model penguatan Pendidikan karakter yang lebih komprehensif. Tujuan penelitian menghasilkan model integrasi pengembangan pendidikan karakter religius berbasis integratif moral. Penelitian menggunakan mix-method yaitu metode kombinasi metode kualitatif dan metode kuantitatif. Instrumen penelitian kualitatif menggunakan peneliti sendiri sebagai instrumen utama sedangkan instrumen kuantitatif menggunakan angket, yang sudah divalidasi. Informan penelitian, penelitian kualitatif menggunakan purposive sampling dan teknik random sampling untuk penelitian kuantitatif. Teknik pengumpulan data menggunakan teknik wawancara, teknik observasi, teknik angket dan teknik dokumentasi. Tahapan analisis data kualitatif dilakukan mulai mereduksi data, mendisplay data, dan melakukan verifikasi data. Hasil penelitian model integrasi pengembangan pendidikan karakter religius yang telah dikembangkan di Universitas Muhammadiyah Makassar terintegrasi dengan integratif moral yaitu knowing, feeling, sinverbal, action, habitus dan culture untuk menanamkan karakter religius kepada mahasiswa dalam enam tingkatan moral mulai dari moral knowing, moral feeling, moral sinverbal, moral action, moral habitus dan moral culture pada level mahasiswa dan civitas akademika Universitas Muhammadiyah Makassar. Kata Kunci: Pendidikan Karakter, Moral sinverbal, Moral habitus, Moral culture, Mahasiswa